Synthesis, spectral and structural characterization of cobalt(III) dithiocarbamato complexes: Catalytic application for the solvent free enamination reaction. (14th December 2015) - Bharati, Pooja; Bharti, A.; Nath, P.; Bharty, M.K.; Butcher, R.J.; Singh, N.K.
Graphical abstract: Three new cobalt(III) complexes, [Co(mpcdt)3 ] (1 ), [Co(ppcdt)3 ] (2 ) and [Co(mppcdt)3 ]·0.25CHCl3 (3 ), of 4-methyl piperazine-1-carbodithioate (mpcdt), 4-phenyl piperazine-1-carbodithioate (ppcdt) and 4-(2-methoxyphenyl) piperazine-1-carbodithioate (mppcdt) have been synthesized and characterized by various physicochemical techniques. The catalytic properties of the above complexes have also been examined. A series of β-enaminoesters and β-enaminones were obtained by the reactions of β-ketoesters and 1, 3-diketones with aliphatic and aromatic amines, using the above cobalt(III) complexes as catalysts, which have been characterized by NMR, GC–MS and X-ray crystallography. Thermogravimetric analysis of complexes1 and2 have been investigated by TG-DTA, which indicate that cobalt sulfide is formed as the final product. Abstract: The syntheses, spectral, structural and catalytic properties of some new cobalt(III) complexes, [Co(mpcdt)3 ] (1 ), [Co(ppcdt)3 ] (2 ) and [Co(mppcdt)3 ]·0.25CHCl3 (3 ), derived from 4-methyl piperazine-1-carbodithioate (mpcdt), 4-phenyl piperazine-1-carbodithioate (ppcdt) and 4-(2-methoxyphenyl) piperazine-1-carbodithioate (mppcdt) have been described. A series of β-enaminoesters and β-enaminones were obtained in about 90% yield by the reactions of β-ketoesters and 1, 3-diketones with aliphatic and aromatic amines using 1–2 mol% of the above cobalt(III) complexes as catalysts and these have been characterized by NMR, GC–MS and X-ray crystallography. Complexes1, 2 and3 are stabilized by intermolecular C–H⋯S interactions, leading to the formation of supramolecular architectures. Thermogravimetric analysis of complexes1 and2 have been investigated by TG-DTA, which indicate that cobalt sulfide is formed as the final product.